ACTUALIZATION OF BANK PRINCIPLES OF PRECAUTION IN AN EFFORTS TO PROTECT CUSTOMERS AGAINST SOCIAL ENGINEERING BANKING CRIME MODES - Johannes Ibrahim Kosasih; I Nyoman Sukandia; AA Ngr Mayun Narindra; I Made Aditya Mantara Putra (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study is based on the increasing cases of socialengineering fraud in the banking sector that threatencustomer security. The urgency of this study lies in theneed to understand how the bank's precautionaryprinciple can be actualized to protect customers fromincreasingly sophisticated crime modes. The purpose ofthis study is to analyze the application of theprecautionary principle in customer protection effortsand to identify steps that can be taken by banks to reducethe risk of such crimes. The research method used is anormative method supported by empirical data. Empiricaldata were collected through in-depth interviews withbank management, namely at PT. Bank BRI DenpasarRenon Branch and PT. Bank BPD Bali Denpasar Branch.The results of the study indicate that although banks haveimplemented several precautionary principles, there arestill gaps in their implementation that can be exploited bycriminals. This study found that customer education andimproving digital security systems are important stepsthat need to be taken to strengthen customer protection.The output of this study is expected to provide practicalrecommendations for banks in optimizing the applicationof the precautionary principle and increasing customerawareness of the potential risks of social engineeringcrimes. In addition, the results of this study can also be areference for better banking policies in protectingcustomers in the digital era